A kind of easy-to-clean, efficient water-in-oil emulsion separation temperature-sensitive intelligent membrane and its preparation method
Patent Information
- Application Number
- CN202311297504.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-09
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-10-09
AI Technical Summary
结果证明含有PNIPAM的膜在温度变化的水清洗辅助下显示出优异的抗污染和自清洁性能,但是该膜的水渗透率较低,最大水渗透率在600Lm-2h-1bar-1左右,限制了其在油水分离领域的应用
[0043]1.本发明提供了一种易清洗、高效油包水乳液分离温敏智能膜,该温敏智能膜由膜基材和温敏智能高分子组成,所述膜基材为有机膜,所述温敏智能高分子是由温敏单体在膜基材中原位聚合形成,温敏智能高分子与膜基材的分子链之间形成了半互穿网络结构,温敏智能高分子主要分布在该智能膜的表面;该温敏智能膜的表面具有若干均匀分布的纳米凸起结构,该温敏智能膜的内部具有膜孔结构;该温敏智能膜的膜孔随着所处环境温度的升高或降低而增大或减小。本发明提供的温敏智能膜对油包水乳液具有优异的分离性能,同时还具有优异的温敏性和水渗透率,非常有利于在油水分离领域应用。
Smart Images

Figure BDA0004483455140000101 
Figure BDA0004483455140000111 
Figure BDA0004483455140000121
Abstract
Description
Technical Field
[0001] This invention belongs to the field of oil-water emulsion separation, and relates to an easy-to-clean, high-efficiency temperature-sensitive membrane for separating water-in-oil emulsions and its preparation method. Background Technology
[0002] In recent years, with the rapid development of machining, industrial production, and the catering industry, the production of water-in-oil emulsions has also increased significantly. The discharge of water-in-oil emulsions not only harms human health and the ecological environment but also wastes resources. Therefore, the separation and recycling of water-in-oil emulsions is crucial. The recovered waste oil can be recycled into industrial oil, plant asphalt, biogas, and biodiesel. However, the water content in the recovered waste oil directly affects the yield and quality of the reused products. For example, in the preparation of biodiesel, a water content of 0.1% in the reactants affects the ester yield, and a water content of 5% almost completely inhibits the reaction. Therefore, the water content of the raw materials is generally required to be below 0.06%. Thus, efficient separation and purification of water-in-oil emulsions is one of the keys to their reuse.
[0003] Compared to other oil-water separation technologies, membrane separation technology offers advantages such as high separation accuracy, small footprint, low energy consumption, and low cost, making it highly favored in the oil-water separation field. Compared to organic membrane materials such as polyethersulfone, polysulfone, and polyacrylonitrile, polyvinylidene fluoride (PVDF) exhibits superior hydrophobicity, mechanical strength, and thermal stability, and is widely used in the preparation of oil-water separation membrane materials. According to the Wenzel surface wetting model, constructing micro / nano structures on the membrane surface can amplify the wettability of the membrane surface and improve the separation efficiency. However, the micro / nano structures and low surface energy of PVDF membranes make them highly susceptible to organic fouling, making cleaning and regeneration difficult. Therefore, the main challenge currently facing PVDF-based oil-water separation technology is balancing membrane separation efficiency and membrane regeneration capability. In practical oil-water separation applications, it is desirable for membranes to have both high separation efficiency and ease of cleaning, thereby extending their service life. Therefore, developing PVDF membranes that are easy to clean and can efficiently separate water-in-oil emulsions is of great significance.
[0004] Currently, strategies for constructing micro / nanostructures on membrane surfaces can be categorized based on different construction principles, including polymer electrospinning, introduction of micro / nano particles, induced crystallization, and the use of rough templates. Compared to polymer electrospinning and the introduction of micro / nano particles, induced crystallization and the use of rough templates offer advantages such as low cost and simple operation. Induced crystallization utilizes the semi-crystalline properties of PVDF to induce nucleation and crystal growth. Researchers have prepared superoleophilic PVDF membranes using ammonia as an inert solvent to induce phase separation. The addition of ammonia causes local microphase separation and nucleation in the solution as PVDF clusters, which gradually grow into spherical crystalline particles during subsequent phase separation. Membranes prepared using this method can effectively separate water-in-oil emulsions, with oil purity exceeding 99.95%. After ethanol washing, the membrane's flux recovery rate after 20 reuses is over 85%. Although induced crystallization is simple, the membrane is prone to transient phase separation during inert solvent-induced phase separation, making it difficult to control the micro / nanostructures on the membrane surface. The strategy of using rough templates involves using rough nonwoven fabrics as physical templates, coating the casting solution onto the nonwoven fabric, and then peeling the membrane off the nonwoven fabric to construct a micro / nano rough structure on the membrane surface. Researchers have used polyester nonwoven fabric as a template to prepare PVDF composite membranes with multi-scale micro / nano structures. When this membrane was used to separate water / chloroform emulsions, water / soybean oil emulsions, and water / n-hexane emulsions, the purity of the filtrate after separation was higher than 99.9%, and after being washed with anhydrous ethanol, its flux did not decrease significantly after 20 reuses. However, the template method for constructing micro / nano structures has drawbacks such as difficulty in peeling and incomplete morphology, which limits its application to some extent. Furthermore, PVDF membranes prepared by the above methods require cleaning and regeneration using organic solvents. Considering the high cost, harmfulness of chemical reagents, and irreversible fouling accumulation, further improving the membrane's cleaning and regeneration performance is essential.
[0005] To address this issue, some researchers have proposed introducing smart polymers into membranes to impart stimulus-responsive self-cleaning properties. For example, some researchers prepared a self-cleaning temperature-sensitive membrane by blending poly(N-isopropylacrylamide-grafted-silica) (PNIPAM-SiO2) with PVDF. This membrane exhibited water permeability of 250 L / m³ at 25°C and 375 L / m³ at 37°C. -2 h -1 bar -1The ratio of high to low temperature permeability is approximately 1.5, and the normalized response coefficient N is 1.2. During the circulating filtration of bovine serum albumin (BSA) solution, the flux recovery rate after rinsing with room temperature pure water is over 85%. When the membrane is cleaned with room temperature pure water, the poly(N-isopropylacrylamide) (PNIPAM) on the membrane surface forms hydrogen bonds with water molecules, becoming hydrophilic and reducing the adhesion to BSA protein molecules, thus regenerating the membrane. However, the membrane's low water permeability and relatively small temperature sensitivity limit its application in practical oil-water separation scenarios. Other researchers have prepared an antifouling, self-cleaning PVDF / nylon-6,6 / PNIPAM temperature-sensitive composite membrane using electrospinning and conventional casting processes. At an operating temperature of 22℃, the fouled membrane was cleaned with 50℃ water. The flux recovery rate of the temperature-sensitive membrane with added PNIPAM reached 96%, and the flux decline rate was only 26%, while the flux recovery rate of the blank control membrane without PNIPAM was only 56%, and the flux decline rate was 36%. Furthermore, the flux recovery rate of cleaning with 50℃ water was superior to that of cleaning with 22℃ water. These results demonstrate that the membrane containing PNIPAM exhibits excellent antifouling and self-cleaning performance with the assistance of water cleaning under temperature variations. However, the water permeability of this membrane is relatively low, with a maximum water permeability of 600 μm. - 2 h -1 bar -1 The inherent hydrophobicity of PVDF membranes limits their application in oil-water separation. Furthermore, existing PVDF membranes for oil-water separation still face challenges in simultaneously achieving high oil-water separation efficiency and easy cleaning and regeneration. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide an easy-to-clean, high-efficiency temperature-sensitive membrane for separating water-in-oil emulsions and its preparation method. This method improves the separation efficiency of water-in-oil emulsions while utilizing the alternating changes in ambient water temperature based on the membrane's temperature-sensitive properties to achieve efficient cleaning and regeneration of the membrane, thereby extending the membrane's service life.
[0007] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is as follows:
[0008] An easy-to-clean, high-efficiency temperature-sensitive smart membrane for separating water-in-oil emulsions is disclosed. This membrane comprises a membrane substrate and a temperature-sensitive smart polymer. The membrane substrate is an organic membrane, and the temperature-sensitive smart polymer is formed by in-situ polymerization of temperature-sensitive monomers within the membrane substrate. A semi-interpenetrating network structure is formed between the molecular chains of the temperature-sensitive smart polymer and the membrane substrate. The temperature-sensitive smart polymer is mainly distributed on the surface of the smart membrane. The surface of the temperature-sensitive smart membrane has several uniformly distributed nano-protrusion structures, and the interior of the membrane has a pore structure. The pore size of the temperature-sensitive smart membrane increases or decreases with the increase or decrease of the ambient temperature.
[0009] In the above-mentioned technical solution for easy-to-clean, high-efficiency oil-in-water emulsion separation temperature-sensitive smart membrane, the mass ratio of temperature-sensitive smart polymer to membrane substrate is 0.8 to 1.0.
[0010] In the above-mentioned technical solution for an easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane, the temperature-sensitive smart polymer is poly(N-isopropylacrylamide).
[0011] In the aforementioned technical solution of an easy-to-clean, high-efficiency temperature-sensitive smart membrane for separating water-in-oil emulsions, the temperature-sensitive smart membrane has a separation efficiency of at least 98% for water-in-oil emulsions, and the water content of the oil phase obtained after separation by the temperature-sensitive smart membrane does not exceed 0.04%. Further, the temperature-sensitive smart membrane has a separation efficiency of at least 99.6% for water-in-oil emulsions, and the water content of the oil phase obtained after separation by the temperature-sensitive smart membrane does not exceed 0.01%.
[0012] In the above-mentioned technical solution of easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane, the membrane flux of the temperature-sensitive smart membrane increases with the increase of temperature within a certain temperature range. For example, the membrane flux of the temperature-sensitive smart membrane increases with the increase of smart membrane temperature within the range of 20 to 45°C.
[0013] In the above-mentioned technical solution of easy-to-clean, high-efficiency oil-in-water emulsion separation temperature-sensitive smart membrane, when the temperature-sensitive smart membrane is contaminated, the temperature of the temperature-sensitive smart membrane is first adjusted to not exceed 25°C, and then the temperature-sensitive smart membrane is repeatedly washed with high-temperature water at 40-45°C and low-temperature water at 20-25°C, so that the temperature-sensitive smart polymer in the temperature-sensitive smart membrane repeatedly contracts and expands, thereby removing the contaminants on the temperature-sensitive smart membrane.
[0014] In the above-mentioned technical solution of easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane, the temperature-sensitive smart membrane has a pore size of 0.3 to 1.0 μm and a porosity of 84% to 95% under room temperature conditions.
[0015] In the above-mentioned technical solution of easy-to-clean, high-efficiency oil-in-water emulsion separation temperature-sensitive smart membrane, the thickness of the temperature-sensitive smart membrane is determined according to the actual application requirements. Typically, the thickness of the temperature-sensitive smart membrane can be 50-100μm.
[0016] In the above-mentioned technical solution of an easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane, the surface roughness R of the temperature-sensitive smart membrane is... a The roughness ranges from 21 to 37 nm, and this roughness was obtained by testing at room temperature.
[0017] In the above-mentioned technical solution of easy-to-clean, high-efficiency oil-in-water emulsion separation temperature-sensitive smart membrane, the size (i.e., height and diameter) of the nano-protrusion structure on the surface of the temperature-sensitive smart membrane is usually no more than 50 nm. For example, the height of the nano-protrusion structure on the surface of the temperature-sensitive smart membrane is generally around 10 nm, and the diameter of the nano-protrusion structure is generally around 40 nm.
[0018] In the above-mentioned technical solution of easy-to-clean, high-efficiency oil-in-water emulsion separation temperature-sensitive smart membrane, the membrane substrate can be adjusted according to actual application requirements. Feasible organic membrane materials include polyvinylidene fluoride (PVDF) and polyethersulfone (PES).
[0019] This invention demonstrates through experiments that the aforementioned easy-to-clean, high-efficiency temperature-sensitive smart membrane for separating water-in-oil emulsions not only exhibits excellent separation performance but also possesses superior temperature sensitivity and water permeability. This is highly advantageous for the application of this temperature-sensitive smart membrane in the field of oil-water separation. For example, the normalized thermal response coefficient N of the temperature-sensitive smart membrane provided by this invention can reach as high as 3.78, while the water permeability at 20°C can reach 2000 L / m³. -2 h -1 bar -1 As temperature increases, water permeability gradually increases, reaching 12500 L / m² at 45℃. -2 h -1 bar -1 above.
[0020] This invention also provides a method for preparing the above-mentioned easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane, comprising the following steps:
[0021] (1) Scraping film
[0022] Adjust the temperature of the glass plate of the film scraping machine to 50-70℃, pour the casting liquid at 50-70℃ onto the glass plate for film scraping, and immediately after scraping, transfer the obtained wet film to a constant temperature and humidity environment at 20-30℃ and 70%-85% relative humidity for 0.25-5 minutes, and then transfer it to a coagulation bath at room temperature to cure the wet film.
[0023] The casting solution is composed of a temperature-sensitive intelligent polymer, a membrane substrate, and a solvent. In the casting solution, the mass ratio of the temperature-sensitive intelligent polymer to the membrane substrate is 0.8 to 1.0, and the molecular chains of the temperature-sensitive intelligent polymer and the membrane substrate have a semi-interpenetrating network structure.
[0024] (2) Washing
[0025] The cured membrane was transferred to deionized water and washed thoroughly to obtain an easy-to-clean, high-efficiency temperature-sensitive smart membrane for separating water-in-oil emulsions.
[0026] In the above preparation method, the medium of the coagulation bath is water.
[0027] In the above preparation method, the preparation method of the casting solution is as follows:
[0028] (1) Preparation of prepolymer solution
[0029] A prepolymer solution is formed by dissolving a thermosensitive monomer, a crosslinking agent, and a membrane substrate in a solvent. In the prepolymer solution, the concentration of the membrane substrate is 0.15–0.2 g / mL, the mass of the thermosensitive monomer accounts for 80%–100% of the mass of the membrane substrate, and the molar amount of the crosslinking agent is 1%–2% of the molar amount of the thermosensitive monomer.
[0030] (2) Preparation of casting solution
[0031] Remove oxygen from the prepolymer solution, add an initiator, and stir the reaction at 70-80°C for 6-10 hours under sealed conditions. Place the resulting reaction solution under vacuum at 50-70°C for 10-12 hours, and then degas to obtain the casting solution. In this step, the amount of initiator added is 1%-3% of the molar amount of the temperature-sensitive monomer.
[0032] In the above preparation method, the temperature-sensitive monomer is N-isopropylacrylamide monomer when preparing the casting solution.
[0033] In the above preparation method, when preparing the casting solution, the crosslinking agent can be N,N′-methylenebisacrylamide, vinyltriethoxysilane (VTES), and the initiator can be azobisisobutyronitrile, azobisisoheptanenitrile (ABVN), azobisisovalerate (AMBN), etc.
[0034] In the above preparation method, when preparing the casting solution, oxygen in the prepolymer solution can be removed by introducing nitrogen gas into the prepolymer solution.
[0035] In the above preparation method, when preparing the casting solution, degassing can be performed by vacuum degassing or stirring degassing.
[0036] In the above-described preparation method, the micro / nano structure of the temperature-sensitive smart membrane surface and the internal pore structure can be controlled by adjusting the process parameters, thereby regulating its oil-in-water emulsion separation performance. For example, by adjusting the ratio of temperature-sensitive monomer to membrane substrate, the degree of crosslinking of the temperature-sensitive monomer, the temperature of the glass plate of the coating machine during coating, the temperature and relative humidity of the constant temperature and humidity environment, and the exposure time in the constant temperature and humidity environment, the micro / nano structure and surface wettability of the prepared temperature-sensitive smart membrane can be flexibly adjusted, thereby achieving flexible control over its oil-in-water emulsion separation performance.
[0037] The formation principle of the temperature-sensitive smart film surface micro / nano structure described in this invention is as follows:
[0038] This invention employs in-situ crosslinking polymerization and vapor-induced phase separation to form a membrane. The temperature-sensitive intelligent polymer is formed by the in-situ polymerization of temperature-sensitive monomers in a membrane substrate. A semi-interpenetrating network structure is formed between the molecular chains of the temperature-sensitive intelligent polymer and the membrane substrate. During the phase separation process, due to the hydrophilic segregation effect of the temperature-sensitive intelligent polymer, the hydrophilic temperature-sensitive intelligent polymer will drive the molecular chains of the membrane substrate to migrate to the membrane surface. Meanwhile, the molecular chains of the temperature-sensitive intelligent polymer repel each other, ultimately forming several uniformly distributed nano-protrusion structures on the membrane surface.
[0039] The mechanism by which the temperature-sensitive smart membrane of this invention separates water-in-oil emulsions and performs temperature-responsive cleaning is as follows:
[0040] In the process of separating water-in-oil emulsions using the temperature-sensitive intelligent membrane described in this invention, due to the oleophilicity of the membrane substrate (such as PVDF), the membrane is first wetted by the continuous phase oil. The high oil content is confined in the columnar structure on the membrane surface. The oil layer between adjacent nano-protrusions on the membrane surface generates Laplace resistance, which hinders water permeation, thereby improving the purity of the filtrate oil and the separation efficiency.
[0041] When the temperature-sensitive smart membrane becomes fouled, due to the thermal response characteristics of the temperature-sensitive smart polymer (such as PNIPAM) in the membrane, it can be repeatedly washed with alternating high-temperature water (e.g., 40–45°C) and low-temperature water (e.g., 20–25°C) to achieve effective cleaning and regeneration. For example, when contaminants adhere to the membrane, first adjust the membrane temperature to room temperature (e.g., not exceeding 25°C), then repeatedly wash it with alternating high-temperature water (e.g., 40–45°C) and low-temperature water (e.g., 20–25°C). During high-temperature water washing, the molecular chains of the temperature-sensitive smart polymer contract, forming a buffer layer on the membrane surface and in the membrane pores, making it easier to remove contaminants. During low-temperature water washing, the molecular chains of the temperature-sensitive smart polymer extend. Repeated alternating washing with high-temperature and low-temperature water causes the molecular chains of the temperature-sensitive smart polymer to frequently contract and extend, forming an elastic interface that promotes efficient removal of contaminants.
[0042] Compared with the prior art, the technical solution provided by the present invention has the following beneficial technical effects:
[0043] 1. This invention provides an easy-to-clean, high-efficiency temperature-sensitive smart membrane for separating water-in-oil emulsions. The membrane consists of a membrane substrate and a temperature-sensitive smart polymer. The membrane substrate is an organic membrane, and the temperature-sensitive smart polymer is formed by in-situ polymerization of temperature-sensitive monomers within the membrane substrate. A semi-interpenetrating network structure is formed between the molecular chains of the temperature-sensitive smart polymer and the membrane substrate. The temperature-sensitive smart polymer is mainly distributed on the surface of the smart membrane. The surface of the temperature-sensitive smart membrane has several uniformly distributed nano-protrusion structures, and the interior of the membrane has a pore structure. The pore size of the temperature-sensitive smart membrane increases or decreases with changes in ambient temperature. The temperature-sensitive smart membrane provided by this invention exhibits excellent separation performance for water-in-oil emulsions, as well as excellent temperature sensitivity and water permeability, making it highly advantageous for applications in the field of oil-water separation.
[0044] 2. Because the surface of the easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane provided by this invention has several uniformly distributed nano-protrusion structures, the presence of these uniformly distributed nano-protrusion structures generates Laplace resistance between the continuous phase layers of adjacent nano-protrusion structures on the membrane surface, hindering the penetration of the dispersed phase and effectively improving the oil-water separation efficiency of the membrane. Experiments have confirmed that the temperature-sensitive smart membrane of this invention achieves a separation efficiency of over 98% for water-in-oil emulsions, and the water content of the oil phase obtained after separation by this temperature-sensitive smart membrane does not exceed 0.04%. In a further preferred embodiment, the separation efficiency of the temperature-sensitive smart membrane for water-in-oil emulsions is over 99.6%, and the water content of the oil phase obtained after separation by this temperature-sensitive smart membrane does not exceed 0.01%, thus achieving highly efficient separation of water-in-oil emulsions.
[0045] 3. When the easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane provided by this invention becomes fouled, the cleaning method is as follows: First, adjust the temperature of the temperature-sensitive smart membrane to not exceed 25°C. Then, repeatedly wash the temperature-sensitive smart membrane with alternating high-temperature water at 40-45°C and low-temperature water at 20-25°C. This causes the temperature-sensitive smart polymers in the membrane to repeatedly contract and expand, thus removing contaminants from the membrane. Experiments have confirmed that, under operating conditions at 20°C, using the above method to alternately wash the fouled membrane with high and low-temperature water achieves a flux recovery rate of over 90% and an irreversible fouling rate of less than 10%. Therefore, the temperature-sensitive smart membrane provided by this invention features simple cleaning operation, low cleaning cost, no secondary pollution, good cleaning effect, and a low irreversible fouling rate. Compared to the existing technology using organic solvents for membrane cleaning, the membrane cleaning method of this invention effectively avoids damage to the membrane from organic solvents and reduces cleaning costs, which is beneficial for industrial applications. Compared to the existing technology using water for membrane cleaning, the membrane cleaning method of this invention has the advantage of better cleaning effect.
[0046] 4. This invention also provides a method for preparing the above-mentioned easy-to-clean, high-efficiency temperature-sensitive smart membrane for separating water-in-oil emulsions. This method employs in-situ crosslinking polymerization and vapor-induced phase separation to form the membrane. The temperature-sensitive smart polymer is formed by in-situ polymerization of temperature-sensitive monomers within the membrane substrate. A semi-interpenetrating network structure is formed between the molecular chains of the temperature-sensitive smart polymer and the membrane substrate. During phase separation, the hydrophilic segregation effect of the temperature-sensitive smart polymer and the mutual repulsion between the molecular chains of the temperature-sensitive smart polymer are utilized to form several uniformly distributed nano-protrusion structures on the membrane surface. Compared to the physical blending method used in the prior art, the in-situ crosslinking polymerization method of this invention is simple to operate, and the semi-interpenetrating network structure of the temperature-sensitive polymer has good bonding performance with the membrane substrate, making it less prone to loss during use. It also exhibits good cycle stability when separating water-in-oil emulsions. Attached Figure Description
[0047] Figure 1 These are scanning electron microscope (SEM) images of the surface and cross-section of the membranes prepared in Examples 1-6.
[0048] Figure 2 These are atomic force microscopy images of the membranes prepared in Examples 1-6.
[0049] Figure 3 These are the infrared spectra of the films prepared in Examples 1 to 6.
[0050] Figure 4 These are scanning electron microscope (SEM) images of the surface and cross-section of the films prepared in Examples 1, 7-9 and Comparative Example 1.
[0051] Figure 5 These are atomic force microscopy images of the films prepared in Examples 1, 7-9 and Comparative Example 1.
[0052] Figure 6 These are the infrared spectra of the films prepared in Examples 1, 7-9 and Comparative Example 1.
[0053] Figure 7 The figures show the air contact angles (Figure a) and oil contact angles (Figure b) of the membranes prepared in Examples 1-6.
[0054] Figure 8 The figures show the air contact angles (Figure a) and oil contact angles (Figure b) of the membranes prepared in Examples 1, 7-9 and Comparative Example 1.
[0055] Figure 9 These are optical and microscopic photographs of the membranes prepared in Examples 1-6 before and after separation of water-in-oil emulsions. Among them, images b1-g1 and b2-g2 are optical and microscopic photographs after separation at 25°C, images b3-g3 and b4-g4 are optical and microscopic photographs after separation at 45°C, and images a1-a2 are optical and microscopic photographs before separation.
[0056] Figure 10 Figure a shows the separation permeability of the membranes prepared in Examples 1-6 to the soybean oil-in-water emulsion (Figure a), as well as the separation efficiency and water content of the filtrate after separation (Figure b).
[0057] Figure 11 These are optical and microscopic photographs of the membranes prepared in Examples 1 and 7-9 before and after separation of water-in-oil emulsions. Among them, images b1-e1 and b2-e2 are optical and microscopic photographs after separation at 25°C, images b3-e3 and b4-e4 are optical and microscopic photographs after separation at 45°C, and images a1-a2 are optical and microscopic photographs before separation.
[0058] Figure 12 Figure a shows the separation permeability (a), separation efficiency, and water content of the filtrate after separation of the membranes prepared in Examples 1, 7-9 to the soybean oil-in-water emulsion.
[0059] Figure 13 Figure a shows the separation permeability (a), separation efficiency, and water content of the filtrate after separation of the membranes prepared in Examples 8, 10-11 to the soybean oil-in-water emulsion.
[0060] Figure 14 Figure a shows the circulating permeability (Figure a) of the oil-water separation of the membrane prepared in Example 8, as well as the separation efficiency and the water content of the filtrate after separation (Figure b).
[0061] Figure 15 The results show the cleaning and regeneration performance of the membrane prepared in Example 8 at 25°C (Figures a-b) and 45°C (Figures c-d).
[0062] Figure 16 This is the water permeability variation curve of the membrane prepared in Example 8 at 20–45°C. Detailed Implementation
[0063] The following examples further illustrate the easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane and its preparation method according to the present invention. These examples are for illustrative purposes only and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the invention are still within the scope of protection of the present invention.
[0064] In the following examples and comparative examples, polyvinylidene fluoride (PVDF) was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd., with a molecular weight M. WThe concentration was 534000. Before use, the solution was vacuum dried at 50℃ for 4 hours to remove moisture. N,N′-methylenebisacrylamide (MBA, 99%), N,N′-dimethylacetamide (DMAc, 99%), Span 80, methylene blue, and benzyl benzoate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Anhydrous ethanol, acetone, and Karl Fischer reagent were purchased from Chengdu Kelong Chemical Reagent Factory. Azobisisobutyronitrile (AIBN, 98%) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Bovine serum albumin (BSA, Mw = 68000) was purchased from Beijing Solbio Technology Co., Ltd. High-purity nitrogen (99.9%) was purchased from Chengdu Qiaoyuan Technology Co., Ltd. N-isopropylacrylamide (NIPAM, 98%) was purchased from TCI (Shanghai) Chemical Industry Development Co., Ltd., and was recrystallized before use to remove polymerization inhibitors for subsequent polymerization. Deionized water was obtained from the Milli-Q Plus water purification system.
[0065] Example 1
[0066] In this embodiment, an easy-to-clean, high-efficiency temperature-sensitive smart membrane for separating water-in-oil emulsions is prepared, and the steps are as follows:
[0067] (1) Preparation of prepolymer solution
[0068] NIPAM monomer and crosslinking agent MBA were dispersed in solvent DMAc, and then PVDF powder was added. The mixture was stirred at 80°C for 5 hours to fully dissolve the components and obtain a prepolymer solution. In the prepolymer solution, the concentration of PVDF was 0.1875 g / mL, the mass of NIPAM monomer accounted for 80% of the mass of PVDF, and the molar amount of crosslinking agent MBA was 2% of the molar amount of NIPAM monomer.
[0069] (2) Preparation of casting solution
[0070] High-purity nitrogen gas was bubbled into the prepolymer solution for 30 minutes to remove oxygen. Then, an initiator solution, obtained by dissolving AIBN in DMAc, was rapidly injected. The reaction was carried out under sealed conditions at 80°C with stirring for 8 hours. During the reaction, the NIPAM monomer reacted with the crosslinking agent and intertwined with the PVDF molecular chains to form a semi-interpenetrating network structure. The resulting reaction solution was placed in a vacuum drying oven at 65°C and -0.1 MPa for 12 hours, and then stirred and degassed for 30 minutes to obtain the casting solution. In this step, the amount of initiator AIBN added was 2% of the molar amount of NIPAM monomer.
[0071] (3) Scraping and washing
[0072] The casting solution temperature was maintained at 65℃ and poured onto a glass plate (the glass plate temperature was 65℃) on a flatbed film scraper for film scraping. The gap between the scraper and the glass plate was controlled to be 200μm. After film scraping, the wet film was quickly transferred to a constant temperature and humidity chamber at 25℃ and 70% humidity. The film was exposed to the steam environment of the constant temperature and humidity chamber for 0.25min. Then the wet film was immediately transferred to a deionized water coagulation bath until it was completely solidified into a film.
[0073] The cured membrane was transferred to deionized water and washed thoroughly to remove residual solvent and unreacted monomers for a total of 48 hours, with the water changed 3 times a day. The washed membrane was then air-dried at room temperature to obtain an easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane. Finally, it was sandwiched with filter paper and stored in a drying cabinet for later use.
[0074] Example 2
[0075] The operation of this embodiment is basically the same as that of embodiment 1, except that step (3) is exposed to the steam environment of the constant temperature and humidity chamber for 0 min.
[0076] Example 3
[0077] The operation in this embodiment is basically the same as that in embodiment 1, except that step (3) involves exposure to the steam environment of the constant temperature and humidity chamber for 0.5 min.
[0078] Example 4
[0079] The operation of this embodiment is basically the same as that of embodiment 1, except that: step (3) is exposed to the steam environment of the constant temperature and humidity chamber for 1 minute.
[0080] Example 5
[0081] The operation of this embodiment is basically the same as that of embodiment 1, except that step (3) involves exposure to the steam environment of the constant temperature and humidity chamber for 5 minutes.
[0082] Example 6
[0083] The operation of this embodiment is basically the same as that of embodiment 1, except that step (3) involves exposing the product to the steam environment of the constant temperature and humidity chamber for 10 minutes.
[0084] The membranes prepared in Examples 1-6 were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), and the results are as follows: Figures 1-2 As shown in the SEM and AFM images, the membranes prepared in Examples 1-3 exhibit a distinct nano-protrusion structure on their surface. However, with increasing exposure time, the nano-protrusion structure gradually disappears, the surface becomes smoother, and micropores appear on the membrane surface. Furthermore, with prolonged exposure time, the cross-sectional structure of the membrane gradually changes from finger-like pores to cellular pores. Figure 2 R in a For the surface roughness data of the membrane, the membrane roughness test was conducted at room temperature. The test procedure was as follows: First, the dried membrane sample was cut into a square with a side length of 1 cm, and then attached to the sample stage. The membrane sample was observed in Scanasyst in air mode with a scanning range of 5 μm × 5 μm. The arithmetic mean roughness (R0) was used as the measurement. a The roughness of the membrane sample was taken as the roughness. Infrared characterization was performed on the membranes prepared in Examples 1-6, and the results are as follows: Figure 3 As shown, with increasing exposure time, 1544cm -1 and 1648cm -1 The absorption peak intensities at each point increased, corresponding to the bending vibration absorption peak of the NH bond in the amide group and the stretching vibration absorption peak of C=O, respectively. This also demonstrates that the exposure time slowed down the phase separation rate, allowing more PNIPAM to migrate to the membrane surface. The membrane thickness, porosity, and pore size of the membranes prepared in Examples 1-6 were tested at room temperature, and the results are shown in Table 1.
[0085] Example 7
[0086] The operation of this embodiment is basically the same as that of embodiment 1, except that the mass of NIPAM monomer accounts for 40% of the mass of PVDF in step (1).
[0087] Example 8
[0088] The operation of this embodiment is basically the same as that of embodiment 1, except that the mass of NIPAM monomer accounts for 100% of the mass of PVDF in step (1).
[0089] Example 9
[0090] The operation of this embodiment is basically the same as that of embodiment 1, except that the mass of NIPAM monomer accounts for 120% of the mass of PVDF in step (1).
[0091] Comparative Example 1
[0092] The preparation of PVDF membrane in this embodiment is basically the same as in Example 1, except that: NIPAM monomer and crosslinking agent are not added in step (1), and initiator is not added in step (2).
[0093] The membranes prepared in Examples 7-9 and Comparative Example 1 were characterized by SEM and AFM at room temperature. The results are as follows. Figures 4-5As shown in the SEM images, with the increase of NIPAM monomer content, the membrane surface gradually changed from a fibrous structure (Comparative Example 1, Example 7) to several uniformly distributed nanoprotrusion structures. When the NIPAM monomer addition amount was 120% of the PVDF mass (Example 9), micropores appeared on the membrane surface. The changes in the AFM image of the membrane are compared with those of the SEM images. Figure 1 To, Figure 5 R in a The data represent the surface roughness of the membrane. The cross-sectional structure of the membrane exhibits a honeycomb-like porous structure with large cavities; the membrane gradually becomes more porous with increasing NIPAM monomer content. Infrared characterization was performed on the membranes prepared in Examples 7-9 and Comparative Example 1, and their structures are as follows: Figure 6 As shown, compared to Comparative Example 1, the membrane with added NIPAM monomer exhibits better performance at a wavenumber of 1544 cm⁻¹. -1 and 1648cm -1 New absorption peaks appeared at the locations, which were the bending vibration peak of NH in the amide group and the stretching vibration peak of the C=O double bond, respectively. With the increase of NIPAM monomer content, the intensity of the absorption peaks at both locations increased, indicating that more PNIPAM was formed on the membrane surface, demonstrating that PNIPAM was successfully introduced into the PVDF membrane substrate via in-situ polymerization. The membrane thickness, porosity, and pore size of the membranes prepared in Examples 7-9 and Comparative Example 1 were tested. All tests were conducted at room temperature, and the results are shown in Table 1. The specific procedure for pore size testing was as follows: a dry circular membrane sample (diameter 1.25 cm) was first fully immersed in perfluoroethyl ether wetting solution. Then, the fully immersed membrane sample was laid flat in the sample tank and compacted with a rubber ring. The membrane thickness and test pressure were set, with the test pressure ranging from 2 to 10 bar depending on the membrane sample conditions. The test temperature was room temperature. Three samples of each membrane were tested, and the average value was taken as the pore size of that membrane.
[0094] Table 1. Membrane thickness, pore size, and porosity of the membranes prepared in Examples 1-9 and Comparative Example 1.
[0095]
[0096]
[0097] Note: All tests were conducted at room temperature.
[0098] Example 10
[0099] The operation of this embodiment is basically the same as that of embodiment 1, except that: in step (1), the mass of NIPAM monomer accounts for 100% of the mass of PVDF, and in step (3), the exposure in the steam environment of the constant temperature and humidity chamber is 0 min.
[0100] Example 11
[0101] The operation of this embodiment is basically the same as that of embodiment 1, except that: in step (1), the mass of NIPAM monomer accounts for 100% of the mass of PVDF, and in step (3), the sample is exposed to the steam environment of the constant temperature and humidity chamber for 0.5 min.
[0102] Example 12: Membrane surface wettability test
[0103] Using a contact angle measuring instrument (DSA25, Germany) The company measured the contact angles of the membranes prepared in Examples 1-9 and Comparative Example 1 with water and oil in air, and the contact angle of water under oil. The results are as follows: Figures 7-8 As shown. The contact angles of water and oil in air, and the contact angle of water in low-density oil, were measured using the seated drop method, while the contact angle of water in high-density benzyl benzoate oil was measured using the bubble trapping method. A 1cm × 1cm dried membrane sample was cut and fixed onto a glass slide, and 2μL of liquid was dropped onto the sample surface using a syringe. Three membrane samples were taken from each membrane for testing, and the results were the average of the three measurements. The results showed that the membrane prepared in Example 8 had the best water contact angle in oil (162.3°). This was because several uniformly distributed nano-protrusion structures were formed on the membrane surface, effectively increasing the oil-locking ability and Laplace resistance of the membrane surface, giving the oil layer formed on the membrane surface better water-repellent ability.
[0104] Example 13: Membrane oil-water separation performance test
[0105] In this embodiment, the oil-water separation performance of the membranes prepared in the above embodiments and Comparative Example 1 was tested, and the steps are as follows:
[0106] (1) Preparation of water-in-oil emulsion
[0107] Add 0.1g of Span80 to 98mL of soybean oil and stir for 1 hour (1000 rpm). -1 Then add 2 mL of deionized water stained with methylene blue, and stir continuously for more than 3 hours to obtain a water / soybean oil emulsion.
[0108] (2) Water-in-oil emulsion separation performance test
[0109] At 25℃ and 45℃ respectively, using an effective filtration area of 1.26×10 -3 m 2 The permeability (P) of the membrane was measured using a sand core filter with a pressure difference of -0.09 MPa. The membrane was cut into circular pieces with a diameter of 5 cm and pre-wetted with the corresponding continuous oil phase for 10 min before separation. Each group of experiments was measured 3 times, and the average value of the 3 measurements was taken as the actual permeability. The permeability was calculated as shown in formula (1):
[0110]
[0111] In equation (1), V is the volume of the filtrate (L), and A is the effective membrane area (m²). 2 ), where t is the filtration time (h) and Δp is the pressure difference (bar).
[0112] The water content of the filtrate after separation was measured using a Karl Fischer water titrator (915Ti-Touch). Before testing, a standard titration was performed three times with 20 μL of deionized water. Then, a 1 mL sample of the filtrate was taken for rapid injection testing. Each filtrate sample was measured three times. The separation efficiency (E) was calculated using formula (2):
[0113] E = (1-C) f / C0)×100% (2)
[0114] In equation (2), C0 and C f These represent the water content of the original solution and the filtrate, respectively.
[0115] The pure PVDF membrane prepared in Comparative Example 1 had a permeability of 0 for separating water-in-oil emulsions due to its small pore size. Optical and microscopic photographs of the membranes prepared in Examples 1-6 before and after separating water-in-oil emulsions are shown below. Figure 9 As shown, images b1–g1 and b2–g2 are optical and photomicrographs after separation at 25°C; images b3–g3 and b4–g4 are optical and photomicrographs after separation at 45°C; and images a1–a2 are optical and photomicrographs before separation. Figure 9 As can be seen, the emulsion before separation was turbid, and the background markings were not clearly visible. The micrograph showed a large number of emulsified water droplets of varying sizes. After membrane separation at different temperatures (25℃ and 45℃), the filtrate became clear, the background markings were clearly visible, and no water droplets were visible in the micrograph. This demonstrates that the membranes prepared in Examples 1-6 can effectively separate water-in-oil emulsions and collect pure oil.
[0116] Figure 10 The membranes prepared in Examples 1-6 exhibited high permeability and separation efficiency for separating water / soybean oil emulsions. The membrane permeability initially decreased and then increased with increasing exposure time in the steam environment of the constant temperature and humidity chamber, consistent with changes in membrane pore size. The membrane prepared in Example 1 showed the best separation efficiency at both 25°C and 45°C, exceeding 99.6%, and the resulting filtrate had a water content of less than 0.01%.
[0117] Optical and microscopic photographs of the membranes prepared in Examples 1, 7-9 before and after separation of water-in-oil emulsions are shown below. Figure 11As shown, images b1–e1 and b2–e2 are optical and photomicrographs after separation at 25°C; images b3–e3 and b4–e4 are optical and photomicrographs after separation at 45°C; and images a1–a2 are optical and photomicrographs before separation. Figure 11 As can be seen, the emulsion before separation was turbid, the background markings were not clearly visible, and numerous emulsified water droplets of varying sizes were present in the micrograph. After membrane separation at different temperatures (25℃ and 45℃), the filtrate prepared by the membranes in Examples 1 and 8 was clear, the background markings were clearly visible, and no water droplets were visible in the micrograph, indicating that both membranes had excellent oil-in-water emulsion separation performance. However, the membrane prepared in Example 9 did not perform as well as the membranes prepared in Examples 1 and 8 in separating oil-in-water emulsions.
[0118] Figure 12 The membranes prepared in Examples 1 and 7-9 exhibit separation permeability and efficiency for water / soybean oil emulsions. The change in membrane permeability for water-in-oil emulsions correlates with the change in membrane pore size. The membranes prepared in Examples 1 and 8 demonstrate good separation efficiency, exceeding 99.6% at both 25°C and 45°C, with the resulting filtrate containing less than 0.01% water. Figure 12 It can also be seen that the membranes prepared in Examples 7 and 8 have similar separation permeability. However, the membrane prepared in Example 8 has higher separation efficiency. This is mainly because the surface of the membrane prepared in Example 8 has a more uniform nano-protrusion structure. This also shows that forming a uniform nano-protrusion structure on the membrane surface is beneficial to improving the separation efficiency of the membrane.
[0119] Figure 13 The membranes prepared in Examples 8 and 10-11 show the separation permeability and separation efficiency of water / soybean oil emulsion. The membrane prepared in Example 10 has a poor separation effect, while the membranes prepared in Examples 8 and 11 have significantly better separation effects.
[0120] Example 14: Cyclic stability test of the membrane
[0121] The separation stability of the membrane prepared in Example 8 to the water-in-oil emulsion (the water-in-oil emulsion prepared in step (1) of Example 13) was tested by alternating cycles of 45°C and 25°C for 6 times. After each separation, the membrane was immersed in anhydrous ethanol and soybean oil for 15 min, respectively. The separation permeability and separation efficiency after 6 cycles are shown in the figure. Figure 14 As shown. By Figure 14It can be seen that after 6 cycles, the membrane prepared in Example 8 did not show a significant decrease in separation permeability at the corresponding temperatures. The dispersion coefficient (ratio of standard deviation to mean) of its cycle permeability at 45℃ and 25℃ were 0.07 and 0.15, respectively. After 6 high and low temperature cycle separations, the separation efficiency of the water-in-oil emulsion remained above 99%, and the water content of the filtrate after separation was below 0.04%, indicating that the membrane prepared in Example 8 has satisfactory cycle stability and can meet the needs of practical separation.
[0122] Example 15: Membrane Cleaning and Regeneration Performance Test
[0123] 1. The gradient temperature rise water permeability of the membrane prepared in Example 8 was tested using a dead-angle filtration device. The effective filtration area of the filtration device was 1.075 × 10⁻⁶. -3 m 2 The pressure difference was 0.05 MPa. First, the membrane was cut into circular pieces with a diameter of 5 cm, then fixed in the filter device and pre-pressurized for 30 min. The permeability of the membrane was calculated by collecting the volume of constant-pressure water flowing through the membrane over a certain period of time, and the calculation formula is shown in Equation (1). Considering that the change in viscosity will affect the permeability and response coefficient of the membrane, the response performance of the membrane is characterized by the normalized thermal response coefficient (N), and its calculation formula is shown in Equation (3). The results show that the normalized thermal response coefficient N of the membrane prepared in Example 8 is 3.78.
[0124]
[0125] In equation (3), N is the normalized thermal response coefficient, and P H and P L These are the transmembrane permeability at high temperature (45℃) and low temperature (20℃), respectively, η. H and η L (mPa s) represent the viscosity of the liquid (water) at high and low temperatures, respectively.
[0126] 2. Under an operating pressure of 0.05 MPa, the clean regeneration performance of the membrane was measured using the same dead-end filtration device, as follows:
[0127] (1) The clean regeneration performance of the membrane was tested under the condition of operating temperature of 20℃: the water permeability of the membrane before fouling was tested by passing a 1 g / L BSA solution through the membrane as a pollutant, the permeability of the BSA solution was tested by cleaning with anhydrous ethanol at 20℃, the water permeability of the membrane was tested by passing a 1 g / L BSA solution through the membrane as a pollutant, the permeability of the BSA solution was tested by alternating cleaning with water at 45℃ and 20℃, the water permeability of the membrane was tested by passing a 1 g / L BSA solution through the membrane as a pollutant, the permeability of the BSA solution was tested by cleaning with water at 20℃, and the water permeability was tested.
[0128] (2) The cleaning and regeneration performance of the membrane was tested at an operating temperature of 45℃: the water permeability of the membrane before fouling was tested by passing a 1 g / L BSA solution through the membrane as a contaminant, the permeability of the BSA solution was tested by cleaning with anhydrous ethanol at 20℃, the water permeability of the membrane was tested by passing a 1 g / L BSA solution through the membrane as a contaminant, the permeability of the BSA solution was tested by alternating cleaning with water at 45℃ and 20℃, the water permeability of the membrane was tested by passing a 1 g / L BSA solution through the membrane as a contaminant, the permeability of the BSA solution was tested by cleaning with water at 20℃, and the water permeability was tested.
[0129] Cleaning with 20°C anhydrous ethanol or water involves immersing the membrane in 20°C anhydrous ethanol or water for 10 minutes, then replacing with fresh 20°C anhydrous ethanol or water, repeating this process three times. The membrane should be rinsed with 20°C water before reuse. Alternating cleaning with 45°C / 20°C water involves first soaking the membrane in 45°C water for 5 minutes, then immediately transferring it to 20°C water for 5 minutes, replacing with fresh water of the appropriate temperature, and repeating this process three times.
[0130] The permeability of water and BSA solution is calculated according to equation (1), and the flux recovery rate (FRR) and reversible fouling rate (DR) are calculated according to equations (4) to (7). r Irreversible pollution rate (DR) ir ) and total pollution rate (DR) t These indicators were used to specifically analyze the impact of different cleaning methods on membrane performance recovery.
[0131] FRR = (P W1 / P W0 (4) × 100%
[0132]
[0133]
[0134] DR t =DR r +DR ir (7)
[0135] In equations (4) to (7), P w0 and P w1 The permeability of the membrane before and after fouling (L m) are respectively. -2 h -1 bar -1 ), P BSA It is the BSA permeability of the membrane when it is fouled (L m). -2 h -1 bar -1 ).
[0136] Figure 15The figures show the cleaning and regeneration performance of the membrane prepared in Example 8 at 25°C (Figures a-b) and 45°C (Figures c-d). Figures a and c show the changes in water and BSA solution permeability under different cleaning modes, while figures b and d show the flux recovery rate (FRR) and reversible fouling rate (DR) under different cleaning modes. r Irreversible pollution rate (DR) ir ) and total pollution rate (DR) t The changes in the four groups of bar charts in Figures b and d are as follows: the cleaning methods corresponding to each group of bar charts from left to right are 20℃ anhydrous ethanol cleaning, 45℃ / 20℃ alternating water cleaning, and 20℃ water cleaning.
[0137] Depend on Figure 15 It can be seen that the cleaning effect varies significantly when the membrane is cleaned alternately with water at 45℃ and 20℃ at different operating temperatures. At an operating temperature of 20℃, when the membrane is fouled and cleaned alternately with water at 45℃ and 20℃, the flux recovery rate (FRR) is 90.56%, and the irreversible fouling rate (DR) is... ir The flux recovery rate (FRR) was 9.44%, which is because the conformation of the PNIPAM thermally responsive polymer in the membrane responds to temperature changes. When the membrane is exposed to high-temperature water, the PNIPAM chains contract, and the membrane pores enlarge (its normalized thermal response coefficient N is 3.78), forming a buffer layer between the contaminants and the membrane, making the contaminants easier to wash away. Frequent switching between 45°C and 20°C water causes the PNIPAM chains in the membrane to contract and extend rapidly, providing a certain mechanical force for washing the membrane surface and pores, promoting further BSA removal. However, at an operating temperature of 45°C, alternating 45°C / 20°C water has a poor cleaning effect on the membrane, with a flux recovery rate (FRR) of 66.79% and an irreversible fouling rate (DR). ir The recovery rate was 33.21%, which is because a buffer layer cannot be formed between the membrane and the contaminants at this temperature. However, the cleaning effect of this method is slightly better than that of cleaning directly with 20°C water. This is likely due to the mechanical force generated by the frequent conformational changes of the PNIPAM chains stimulated by alternating 45°C / 20°C water. Although the recovery performance of the membrane when cleaned with alternating 45°C / 20°C water is slightly inferior to that when cleaned with anhydrous ethanol, the 45°C / 20°C water cleaning method is low-cost and environmentally friendly, which is beneficial for the application of membranes in practical separation scenarios.
[0138] Figure 16 The graph shows the water permeability variation curve of the membrane prepared in Example 8 from 20°C to 45°C. As can be seen from the graph, the water permeability of the membrane changes significantly with temperature. Under a working pressure of 0.05 MPa, the water permeability of the membrane at 45°C is more than 6 times that at 20°C.
Claims
1. A temperature-sensitive intelligent membrane for easy cleaning and high-efficiency oil-in-water emulsion separation, characterized in that, This temperature-sensitive smart membrane is composed of a membrane substrate and a temperature-sensitive smart polymer. The membrane substrate is an organic membrane, and the temperature-sensitive smart polymer is formed by in-situ polymerization of temperature-sensitive monomers in the membrane substrate. A semi-interpenetrating network structure is formed between the molecular chains of the temperature-sensitive smart polymer and the membrane substrate. The temperature-sensitive smart polymer is mainly distributed on the surface of the smart membrane. The surface of the temperature-sensitive smart membrane has several uniformly distributed nano-protrusion structures, and the interior of the temperature-sensitive smart membrane has a membrane pore structure. The pores of the temperature-sensitive smart membrane increase or decrease with the increase or decrease of the ambient temperature. The mass ratio of the temperature-sensitive intelligent polymer to the membrane substrate is 0.8~1.0; the temperature-sensitive intelligent polymer is a poly( N - Isopropylacrylamide); the membrane substrate is polyvinylidene fluoride; the surface roughness of the temperature-sensitive smart membrane R a The nanoscale diameter is 21~37 nm; the height and diameter of the nanoprotrusion structure do not exceed 50 nm. The temperature-sensitive smart film is prepared by the following method: (1) Scraping film Adjust the temperature of the glass plate of the coating machine to 50~70ºC, pour the casting solution at 50~70ºC onto the glass plate for coating, and immediately after coating, transfer the resulting wet film to a constant temperature and humidity environment at 20~30ºC and 70%~85% for 0.25~0.5 min, and then transfer it to a coagulation bath at room temperature to cure the wet film. The casting solution is composed of a temperature-sensitive intelligent polymer, a membrane substrate, and a solvent. The mass ratio of the temperature-sensitive intelligent polymer to the membrane substrate in the casting solution is 0.8~1.0, and the molecular chains of the temperature-sensitive intelligent polymer and the membrane substrate have a semi-interpenetrating network structure. The preparation method of the casting solution is as follows: A prepolymer solution is formed by dissolving a thermosensitive monomer, a crosslinking agent, and a membrane substrate in a solvent. In the prepolymer solution, the concentration of the membrane substrate is 0.15–0.2 g / mL, the mass of the thermosensitive monomer accounts for 80%–100% of the mass of the membrane substrate, and the molar amount of the crosslinking agent is 1%–2% of the molar amount of the thermosensitive monomer. Oxygen is removed from the prepolymer solution, an initiator is added, and the mixture is stirred and reacted at 70–80 °C for 6–10 h under sealed conditions. The resulting reaction solution is then placed under vacuum at 50–70 °C for 10–12 h, followed by degassing to obtain a casting solution. The amount of initiator added is 1%–3% of the molar amount of the thermosensitive monomer. The thermosensitive monomer is… N -Isopropylacrylamide monomer; (2) Washing The cured membrane was transferred to deionized water and washed thoroughly to obtain an easy-to-clean, high-efficiency temperature-sensitive smart membrane for separating water-in-oil emulsions.
2. The easy-to-clean, high-efficiency oil-in-water emulsion separation temperature-sensitive smart membrane according to claim 1, characterized in that, The temperature-sensitive smart membrane has a separation efficiency of at least 98% for water-in-oil emulsions, and the water content of the oil phase obtained after separation by the temperature-sensitive smart membrane does not exceed 0.04%.
3. The easy-to-clean, high-efficiency water-in-oil emulsion separation temperature-sensitive smart membrane according to claim 1, characterized in that, After the temperature-sensitive smart membrane becomes contaminated, its temperature is first adjusted to not exceed 25 ºC. Then, the membrane is repeatedly washed with alternating high-temperature water at 40~45ºC and low-temperature water at 20~25 ºC. This causes the temperature-sensitive smart polymers in the membrane to repeatedly contract and expand, thereby removing the contaminants from the membrane.